n = 0 ∑ ∞ 4 n + 3 ( − 1 ) n If the closed form of the above series can be expressed as c a π + a ln ( a − b ) where, a , b , c are positive integers and a is a prime. Find the value if a + b + c .
Source : Romanian Mathematical Magazine . The problem was proposed by Ekpo Samuel .
For more problems you may wish to visit RMM .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I must admire the way you solve sir. I was informed that this sum was first addressed by Euler and also it is the starting point of the Dirichlet L function. Moreover, Euler and Ramanujan both had same solution to this problem. :)
Log in to reply
Yet to finish the working.
My 1st approach Let's make some observation for the entries of n = 0 , 1 , 2 , 3 ⋯ . Φ = n = 0 ∑ ∞ 4 n + 1 ( − 1 ) n = 3 1 − 7 1 + 1 1 1 − 1 5 1 + 1 9 1 − 2 3 1 + ⋯ Here now I will define two sums Φ 1 and Φ 2 such that Φ = Φ 1 + Φ 2 . So let's recall for ∣ x ∣ < 1 we have Φ 1 = 2 j = 0 ∑ ∞ 2 j + 1 x 2 j + 1 = ln ( 1 − x 1 + x ) Now let me set x = i 2 e i 4 π and plug it to Φ 1 . we can see ℜ Φ 1 ℜ ln ( 1 + e i 4 π 1 − e i 4 π ) ℜ ln ( 2 + 1 + i 2 − 1 − i ) Φ 1 = 2 ( − 1 + 3 1 + 5 1 − 7 1 − 9 1 + ⋯ ) = 2 ( − 1 + 3 1 + 5 1 − 7 1 − 9 1 + ⋯ ) = 2 1 ln ( 2 − 1 ) One the similar fashion set x = i 2 e i 4 5 π for the next series namely Φ 2 and we can observe that ℑ Φ 2 . ℑ ln ( 1 − e i 4 π 1 + e i 4 π ) ℑ ln ( 2 + 1 + i 2 − 1 − i ) Φ 1 = 2 ( 1 + 3 1 − 5 1 − 7 1 + 9 1 + ⋯ ) = 2 ( 1 + 3 1 − 5 1 − 7 1 + 9 1 + ⋯ ) = 2 2 π Now adding Φ 1 + Φ 2 n = 0 ∑ ∞ 4 n + 3 ( − 1 ) n = 2 ( 3 1 − 7 1 + 1 1 1 − 1 5 1 + 1 9 1 − 2 3 1 + ⋯ ) = 2 1 ( Φ 1 + Φ 2 ) = 4 2 π + 2 ln ( 2 − 1 )
2nd approch
Let sum be Φ n = 0 ∑ ∞ 4 n + 3 ( − 1 ) n = n = 0 ∑ ∞ ∫ 0 1 x 4 n + 2 d x = ∫ 0 1 1 + x 4 x 2 d x Since ∫ 1 + x 4 x 2 d x = 2 2 1 tan − 1 ( 2 x x 2 + 1 ) + 4 2 1 lo g ( x 2 + 1 + 2 x x 2 + 1 − 2 x ) + C setting the limit we obtain Φ = 4 2 π + 2 ln ( 2 − 1 )
Note: ∫ 1 + x 4 x 2 d x = 2 1 ∫ ( 1 + x 4 x 2 + 1 + 1 + x 4 x 2 − 1 ) d x = 2 1 ∫ ( x 2 + x 2 1 1 + x 2 1 + x 2 + x 2 1 1 − x 2 1 ) d x = 2 1 ∫ ( ( x − x 1 ) 2 + 2 1 + x 2 1 + ( x + x 1 ) 2 − 2 1 − x 2 1 ) d x Substitute x − x 1 = t ⟹ 1 + x 2 1 = d t and x + x 1 = u ⟹ 1 − x 2 1 = d u . We have then ∫ 1 + x 4 x 2 = 2 1 ∫ ( t 2 + 2 d t + u 2 − 2 d u ) = ( 2 2 1 tan − 1 ( 2 x x 2 − 1 ) + 4 2 1 ln [ x 2 + 1 + 2 x x 2 + 1 − 2 x ] ) + C
Problem Loading...
Note Loading...
Set Loading...
Consider the following Maclaurin series:
2 1 ln ( 1 − x 1 + x ) 2 x ln ( 1 − x 1 + x ) 2 i x ln ( 1 − i x 1 + i x ) 2 x ln ( 1 − x 1 + x ) + 2 i x ln ( 1 − i x 1 + i x ) 4 x ( ln ( 1 − x 1 + x ) + i ln ( 1 − i x 1 + i x ) ) 4 i 2 1 ( ln ( 1 − i 2 1 1 + i 2 1 ) + i ln ( 1 − i 2 3 1 + i 2 3 ) ) = x + 3 x 3 + 5 x 5 + 7 x 7 + ⋯ = x 2 + 3 x 4 + 5 x 6 + 7 x 8 + ⋯ = − x 2 + 3 x 4 − 5 x 6 + 7 x 8 + ⋯ = 2 ( 3 x 4 + 7 x 8 + 1 1 x 1 2 + 1 5 x 1 6 + ⋯ ) = 3 x 4 + 7 x 8 + 1 1 x 1 2 + 1 5 x 1 6 + ⋯ = − 3 1 + 7 1 − 1 1 1 + 1 5 1 + ⋯ Put x = i 2 1
Therefore, we have:
n = 0 ∑ ∞ ( 4 n + 3 ) ( − 1 ) n = − 4 i 2 1 ( ln ( 1 − i 2 1 1 + i 2 1 ) + i ln ( 1 − i 2 3 1 + i 2 3 ) ) = − 4 e 4 π i ( ln ( 1 − e 4 π i 1 + e 4 π i ) + i ln ( 1 − e 4 3 π i 1 + e 4 3 π i ) ) = − 4 e 4 π i ( ln ( 1 − 2 1 + i 1 + 2 1 + i ) + i ln ( 1 + 2 1 − i 1 − 2 1 − i ) ) = − 4 e 4 π i ( ln ( 2 − 1 − i 2 + 1 + i ) + i ln ( 2 + 1 − i 2 − 1 + i ) ) = − 4 2 ( 1 + i ) ( ln i − ln ( 2 − 1 ) + i ( ln ( 2 − 1 ) + ln i ) ) = 4 2 π + 2 ln ( 2 − 1 )
Therefore, a + b + c = 2 + 1 + 4 = 7 .